USE of GUM Arabic as a Superplasticizer in SelfCompacting Concrete - Athman, Caroline M.; Abuodha, Silvester O.; Nyomboi, Timothy (Blue Eyes Intelligence Engineering & Sciences Publication Pvt. Ltd., 2018)
In this paper, Gum Arabic (GA) obtained from Acacia Senegal trees found in northern Kenya and most of other semi arid areas in Kenya was used in self compacting concrete as a superplasticizer. The research sought to establish the effect of Gum Arabic on concrete rheology at varying dosages and waterpowder ratio. Series of mix design trials were conducted based on European Standard for design of self-compacting concrete (EFNARC). The final optimum mix design ratio applied were: water-powder ratio of 1.1, 1.0, 0.9 and 0.8 and Gum Arabic dosages of 2%, 4%, 6%, 8%, 10% and 12% by weight of cement while the coarse and fine aggregates content applied was 28% and 45% respectively. The resultant mix was tested for passing ability, flow ability and segregation resistance .The results show that Gum Arabic is suitable for use as a superplasticizer in self compacting concrete and a dosage of 8% by weight of cement for water-powder ratio of 1.0, 0.9 and 0.8 by volume and aggregate ratio of 28% coarse and 45% fine is recommended. It is also noted that it has an advantage of being environment friendly.
Keywords: Gum Arabic; Superplasticizer; Spread Flow